Game-Based Learning for Primary English Language Education: A Systematic Literature Review - Suldianti, Vinsensia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Learning English language through game-based method is beneficial, particularly for beginners. Game-based learning techniques, like gamification, serious games, and mobile games, can enhance language proficiency in areas like grammar, vocabulary, and reading comprehension. This systematic literature review critically synthesizes past literature to create an understanding of the application and effectiveness of GBL strategies for English language learning. Criteria were proposed in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) declaration and guidelines, and after final scrutiny, 5 articles were shortlisted for review. The findings shown that GBL techniques, like gamification, serious games, and mobile games, can enhance language proficiency in areas like grammar, vocabulary, and reading comprehension. The findings of this systematic review can help language instructing institutions to emphasize game-based learning to enhance the motivation, students’ personalized learning experiences, and achievement in the learning process. Furthermore, it can be helpful for instructors of the English language, and they can realize the importance of GBL in for Primary English Language Education.